Exploration of Students' Understanding of Geometry Concepts - Rio Fabrika Pasandaran; Indah Suciati; Alfisyahra Alfisyahra (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2021)
This article contains an exploration of conceptual understanding in geometry lectures in the Elementary School Teacher Education Study Program, Cokroaminoto Palopo University, Odd Semester, Academic Year 2020/2021. This research was conducted through a qualitative approach with the aim of explaining the details of the relationship between concepts in detail and recommending appropriate learning in problem solving. Data were collected using observation, documentation, and written tests. The three techniques are elaborated with the aim of analyzing the concepts and problem-solving patterns of the students' final semester test results. The results of the study explain several findings, namely, Teaching geometry should begin with the process of identifying the important concepts that build up a particular problem. These concepts are then analyzed and linked to one another to form a network. The concept network is then represented in an image/visual display. Through this visual display, lecturers can guide students in compiling procedural steps based on the sequence of concepts that have been compiled. Lecturers need to create meaningful learning for students by connecting previous knowledge with new knowledge through various representations, examples, and manipulations and focus on conceptual understanding rather than procedures or rules.Eksplorasi Pemahaman Konsep Geometri MahasiswaArtikel ini memuat eksplorasi pemahaman konsep dalam perkuliahan geometri pada Program Studi Pendidikan Guru Sekolah Dasar Universitas Cokroaminoto Palopo Semester Ganjil Tahun Akademik 2020/2021. Penelitian ini dilakukan melalui pendekatan kualitatif dengan tujuan untuk menjelaskan rincian hubungan antar konsep secara detail, dan merekomendasikan pembelajaran yang tepat dalam pemecahan masalah. Data dikumpulkan menggunakan teknik observasi, dokumentasi, dan tes tertulis. Ketiga teknik tersebut dielaborasi dengan tujuan Hasil penelitian menjelaskan beberapa temuan yakni; pengajaran geometri harus diawali dengan proses identifikasi konsep-konsep penting yang membangun masalah tertentu. Konsep-konsep tersebut selanjutnya dianalisis dan dihubungakan satu sama lain sehingga membentuk sebuah jejaring. Jejaring konsep selanjutnya direpresentasikan ke dalam gambar/tampilan visual. Melalui tampilan visual ini, dosen dapat membimbing mahasiswa dalam menyusun langkah-langkah prosedural berdasarkan urutan konsep yang telah disusun. Dosen perlu menciptakan pembelajaran yang bermakna bagi mahasiswa dengan cara menghubungkan pengetahuan sebelumnya dengan pengetahuan yang baru melalui berbagai representasi, contoh, dan manipulasi dan fokus pada pemahaman konseptual dibandingkan prosedur atau aturan.